THE ROLE OF LEADERSHIP AND WORK DISCIPLINE ON COMPETENCY AND ITS IMPLICATIONS ON THE PERFORMANCE OF ELEMENTARY SCHOOL TEACHERS IN PAGELARAN DISTRICT, PANDEGLANG REGENCY - Yuliawati, Teti; Rustandi, Tata; Permana, Angrian (Yayasan Education and Social Center, 2025)
The results of the first hypothesis test showed no influence of leadership on teacher performance at SDN Teachers in Pagelaran District. This result does not support the proposed hypothesis (rejected) The results of the second hypothesis test showed a significant positive influence of work discipline on teacher performance at SDN Teachers in Pagelaran District. This result supports the proposed hypothesis (accepted). The results of the third hypothesis test showed no influence of competence on teacher performance at SDN Teachers in Pagelaran District. This result does not support the proposed hypothesis (rejected). The results of the fourth hypothesis test showed a positive and significant influence of leadership on competence at SDN Teachers in Pagelaran District. This result supports the proposed hypothesis (accepted). The results of the fifth hypothesis test showed a significant positive influence of work discipline on competence at SDN Teachers in Pagelaran District. This result supports the proposed hypothesis (accepted). The results of the sixth hypothesis test showed that competence could not mediate the influence of leadership on teacher performance at SDN Teachers in Pagelaran District. This result does not support the proposed hypothesis (rejected). The results of the seventh hypothesis test showed that competence could mediate the influence of work discipline on teacher performance at SDN Teachers in Pagelaran District. This result supports the proposed hypothesis (accepted). This study provides important insights for improving the performance of teachers at SDN Pagelaran District, Pandeglang Regency by emphasizing the importance of humanistic leadership, improving teacher performance and creating a better work environment. This strategy can create more productive teacher performance.